The Influence of Advertising Creativity, Advertising Attractiveness, Brand Ambassador Credibility, and Trust on Purchase Intention in The Tokopedia Application(Study of Ads:Selalu Ada,Selalu Bisa) - Jolanda Laurie; Sukaris Sukaris (INNOVATION RESEARCH JOURNAL, 2022)
This study aims to determine the effect of Advertising Creativity, Advertising Attractiveness, Brand Ambassador Credibility, and Trust on buying interest in the Tokopedia application. Researchers used quantitative methods and used Non-Probability sampling technique which was determined based on purposive sampling. Sampling came from 100 respondents of UMG Management Students class 2018-2021 by distributing questionnaires. Tests using the SPSS method, and analysis testing using test instruments, classical assumption tests, and hypothesis testing. The results show that advertising creativity, fish attractiveness, relying on brand ambassadors and trust have a positive and significant effect on buying interest in the Tokopedia application.